Pengaruh Struktur Modal, Keputusan Investasi, Profitabilitas Sebagai Variabel Intervening Terhadap Nilai Perusahaan - Tithania Charisma Putri; Ratih Puspitasari (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine the effect of capital structure and investment decisions through profitability on firm value in food and beverage companies on the Indonesia Stock Exchange for the period 2018-2020. The research sample consisted of 10 food and beverage companies listed on the Indonesia Stock Exchange and selected by purposive sampling. The research data is secondary data obtained from the Indonesia Capital Market Directory (ICMD) in 2018-2020. Analysis of the data used is a path analysis technique to see the effect of capital structure and investment decisions through profitability on firm value. The results showed that the capital structure had no effect on profitability; Investment decisions affect profitability; Capital structure has an effect on firm value; Investment decisions have no effect on firm value; Profitability has an effect on firm value; Capital structure, investment decisions, profitability have a simultaneous effect on firm value. Keywords: Capital Structure, Investment Decision, Profitability, Firm Value.